(untitled) (Raparin Journal of Humanities (RJH), 2020)
The curriculum comes at the forefront of the procedures concerned with academic writing, and most of it needs to be scrutinized and scrutinized in its work, as the application of critical curricula and how to address literary texts requires the critic to take his own course that defines the course of criticism in it, accordingly the study monitored the completed university theses On Modern Arab Poetry in the Universities of the Region (2003-2013), to show the features of those critical practices if they literally applied or departed from the monetary approaches followed, and how it is going to build a specific and specific monetary framework that has certain aspects that bring it together with different samples, and its ability Rest assured The reader on her methods.